Circulating Naturally-Occurring Anticoagulants before Treatment and after Recovery from SARS-CoV-2 Infection in Ghana - Charles Nkansah; Lawrence D. Agyemang; Felix Osei-Boakye; Samuel K. Appiah; Kofi Mensah; Gabriel Abbam; Simon B. Bani; Samira Daud; Hisham A. Osumanu; Charles A. Derigubah; Dorcas Serwaa; Francis A. Apodola; et al. (Ital Publication, 2022)
Background: Disturbance in naturally-occurring anticoagulants may contribute to the hypercoagulable state in COVID-19. This study determined the plasma antigen levels of protein C (PC), protein S (PS), antithrombin-III (AT-III), and thrombomodulin (TM) before treatment and after recovery from COVID-19. Materials and Methods: This cross-sectional study, conducted from February to August 2022 at Kumasi South Hospital, recruited sixty-five RT-PCR-confirmed COVID-19 participants. A venous blood sample was taken for full blood count (FBC) analysis using a 3-part fully automated haematology analyzer, and PC, PS, AT-III, and TM antigen levels measured using ELISA. The data were analyzed using SPSS version 26.0. P<0.05 was considered statistically significant. Results: Severe COVID-19 participants had relatively lower haemoglobin (p<0.001), RBC (p<0.001), HCT% (p<0.001) and platelets (p<0.001), but higher RDW-CV% (p=0.013), WBC (p<0.001), and absolute lymphocyte counts (p<0.001) compared to those with the non-severe form of the disease. The overall prevalence of anaemia among the participants was 58.5%, and 32 (84.2%) and 6 (15.8%) of the anaemic participants had mild and moderate anaemia respectively. Protein C (p<0.001), PS (p<0.001) and ATIII (p<0.001) levels were lower among the severe COVID-19 participants than in the non-severe group. But severe COVID-19 group had higher TM levels (p<0.001) than the non-severe group. Again, participants had higher haemoglobin (p<0.001), RBC (p<0.001), HCT% (p=0.049), absolute neutrophil count (p<0.001) and platelets (p<0.001) after recovery from COVID-19 than the values on admission. Additionally, after recovery, participants had higher levels of PC (p<0.001), PS (p<0.001), and ATIII (p<0.001), but reduced TM (p<0.001). Conclusion: Severe COVID-19 patients had higher PC, PS, and AT-III, but lower TM levels. The changes in circulating anticoagulants may contribute to the hypercoagulable state of COVID-19. Blood cell indices are negatively affected during COVID-19. Complete recovery from the SARS-CoV-2 infection normalised the haematological indices. Assessment of naturally-occurring anticoagulants and the provision of anticoagulants are recommended in the management of COVID-19.   Doi: 10.28991/SciMedJ-2022-04-04-01 Full Text: PDF